Large tree structure visualization and display system - Avi Halachmi; Michael Jacovi; Menachem Shtalhaim; Sigalit Ur; Yoelle Maarek (2000)
System for the visualization of a large tree structure in which the selection of a center object (40) amongst the objects of the large tree structure enables n levels of descendants from the center object to be visualized on a screen together with the center object, the system has a visualization control in computer memory enabling the objects of a given level corresponding to the children of a parent object of the immediate higher level to be visualized in a fan-shaped area centered around the parent object. A scrollbar associated with the parent object enables all the children of a parent object to be scrolled in a fan. Fan control buttons on the screen enable the aperture of the fans to be modified so that a variable number of children can be visualized in each fan.